Sosialisasi dan Pelatihan Pengolahan Limbah Pangan menjadi Eco-enzyme di Lingkungan Sekolah - Nurenik, Nurenik; Indarwati, Lisa Dwifani; Rastono, Adi; Muzadi, Masrur (Indonesian Journal for Social Responsibility, 2025)
Each year, food waste from households, markets, restaurants, and schools continues to increase. Improper management of this waste can harm the environment and contribute to greenhouse gas emissions. A simple, low-cost, and environmentally friendly solution for managing food waste is to process it into an eco-enzyme. This community engagement program aimed to enhance students’ knowledge and skills in creating eco-enzymes as a practical approach to addressing food waste issues. The activity was conducted at MA Islamiyah Kedungjambe in Tuban and involved 39 students from the XI grade, focusing on both science and social studies tracks. The methods used included interactive socialization and hands-on training in eco-enzyme production, utilizing a mixture of fruit peels, brown sugar, and water in a 3:1:10 ratio, followed by a three-month fermentation process. The resulting eco-enzyme had a fresh, fermented aroma and was free from unpleasant odours. It can be used as a liquid organic fertilizer for plants. The results indicated high enthusiasm among participants, along with a significant increase in their understanding and interest in making eco-enzymes independently at home. This activity effectively fostered environmental awareness among students and is recommended for implementation in other schools as part of sustainable environmental education.